Analysis of Causing Factors on Teachers’ Code Switching - Triana Novitasari; Dian Erlina; Fitri Alya Okta Sukma (UNIB Press, 2022)
Code switching is an intriguing phenomenon to investigate because it is a part of the development process and the use of multiple languages (bilingual). In the world of education, both at the middle and upper levels, the use of code switching can be done by teachers or students in the classroom. This research was conducted to find out the factors causing teachers to do code switching in the classroom. The research method applied in this study was qualitative research in the form of a case study. The writers selected the participants for this research by using a convenience sampling technique. There were two teachers of English at SMA Negeri 15 Palembang, and those teachers were selected as the participants to collect the data. In collecting data, the writers used interviews through open-ended questions. Then, the writers analyzed the data obtained from the interview using a theme code system in the form of table codes, synchronizing the data with the aspects and items that prevailed in the interview protocol. The result of this research based on the interviews showed that there are two factors causing teachers to do code switching. Two factors are linguistics and non-linguistics. Language linguistics factors are divided into language stagnation and a lack of students’ knowledge of vocabulary. Furthermore, non-linguistical factors are divided into the emotional condition of the teacher and the condition of the class situation. Keywords: Code Switching; Actors of Code Switching; Linguistics; Non-Linguistics.